Association of pharmacokinetics and pharmacogenomics with safety and efficacy of gefitinib in patients with EGFR mutation positive advanced non-small cell lung cancer. (March 2016) - Hirose, Takashi; Fujita, Ken-ichi; Kusumoto, Sojiro; Oki, Yasunari; Murata, Yasunori; Sugiyama, Tomohide; Ishida, Hiroo; Shirai, Takao; Nakashima, Masanao; Yamaoka, Toshimitsu; Okuda, Kentaro; Ohmori, Tohru; et al.
Highlights: Elevated gefitinib exposure might be associated with drug-induced ILD. Pharmacokinetics and pharmacogenomics were not associated with toxicity of gefitinib. Pharmacokinetics and pharmacogenomics were not associated with efficacy of gefitinib. Abstract: Objectives: Gefitinib is a potent epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor and is a key drug for patients with EGFR mutation-positive advanced non-small cell lung cancer (NSCLC). The pharmacokinetics of orally administered gefitinib varies greatly among patients. We prospectively evaluated the association of pharmacokinetics and pharmacogenomics with the safety and efficacy of gefitinib in patients with EGFR mutation-positive advanced NSCLC. Patients and methods: Pharmacokinetics was evaluated with samples of peripheral blood obtained on day 1 before treatment and 1, 3, 5, 8, and 24 h after gefitinib (250 mg per day) was administered and on days 8 and 15 as the trough values. The plasma concentration of gefitinib was analyzed with high-performance liquid chromatography. The genotypes of ABCG2, ABCB1, CYP3A4, CYP3A5, and CYP2D6 genes were analyzed with direct sequencing. Results: The subjects were 35 patients (21 women; median age, 72 years; range, 53 to 90 years) with stage IV adenocarcinoma harboring EGFR mutations. The median peak plasma concentration ( C max ) was 377 (range, 168–781) ng/mL. The median area under the curve (AUC) of the plasma concentration of gefitinib from 0 to 24 h was 4893 (range, 698–13991) ng/mL h. The common adverse events were skin toxicity (68% of patients), diarrhea (46%), and liver injury (63%). One patient died of drug-induced interstitial lung disease (ILD). The overall response rate was 82.9% (95% confidence interval, 66.4%–93.4%). The median progression-free survival time was 10 months, and the median survival time was 25 months. The pharmacokinetics and pharmacogenomics were not associated with significantly different toxicities, response rates, or survival times with gefitinib. However, the AUC and C max were highest and the trough value on day 8 was the second highest in one patient who died of drug-induced ILD. Conclusion: Elevated gefitinib exposure might be associated with drug-induced ILD.